2019
DOI: 10.1557/mrc.2018.188
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical and swelling properties of three-dimensional-printed poly (ethylene glycol) diacrylate/silica nanocomposites

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…Additive manufacturing, also called 3D printing, is a distinguished technique for its unparalleled freedom to create complex geometries, circumventing traditional sophisticated and expensive molding and tooling routes . This mold‐free fabrication process is evolving rapidly to provide materials with undiscovered functions and improved properties from microscale to macroscale.…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing, also called 3D printing, is a distinguished technique for its unparalleled freedom to create complex geometries, circumventing traditional sophisticated and expensive molding and tooling routes . This mold‐free fabrication process is evolving rapidly to provide materials with undiscovered functions and improved properties from microscale to macroscale.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, one-dimensional ATP and two-dimensional OMMT hindered the curing process, thus affecting the material properties. Other studies also showed a minimal effect in cure rate and improvement in mechanical and thermal properties up to 10 wt.% (with minimum agglomeration) for SiO 2 filled composites [ 9 , 172 , 175 ].…”
Section: Reinforcements In 3d Printed Partsmentioning
confidence: 96%
“…Conversely, DIW, SLA and DLP use liquid raw materials. Ultrasonication is the most common method to achieve the optimal dispersion of nanomaterials in liquid-based raw materials [ 236 , 238 , 239 , 240 ], although other mechanical mixing methods have also been used [ 229 ]. Sometimes, when the viscosity is high, a solvent is added, which promotes dispersion of the nanomaterial [ 237 ].…”
Section: Additive Manufacturing Of Bone Tissue-engineered Scaffoldmentioning
confidence: 99%